2014
DOI: 10.1016/j.rpor.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Radio-chemotherapy in anal cancer: Institutional experience at a large radiation oncology center in Chile

Abstract: Our findings show that results at the Instituto de Radiomedicina in Chile are comparable to published literature. Dismal results in stage IIIb cases indicate much work remains in therapies to achieve loco-regional control in locally advanced cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Today, a vast amount of clinical experience from single‐institution trials as well as prospective clinical trials on primary organ preserving treatment is available . Multimodality organ‐preservation treatment has become the treatment of choice for many tumor entities . Nevertheless, the issue of conservative treatments versus cystectomy for bladder cancer remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Today, a vast amount of clinical experience from single‐institution trials as well as prospective clinical trials on primary organ preserving treatment is available . Multimodality organ‐preservation treatment has become the treatment of choice for many tumor entities . Nevertheless, the issue of conservative treatments versus cystectomy for bladder cancer remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…With a median follow-up of 56 months, with a minimum of at least 24 months, at 5 years the authors found both OS and DFS of 45%. 33 In our study, we analyzed a population of 27 patients affected by anal carcinoma treated with primary radiochemotherapy based on 5-FU associated with MMC or CDDP (FUMIR vs. PLAFUR schedules).…”
Section: Discussionmentioning
confidence: 99%